Pemanfaatan Teknologi Analisis Data Dan Algoritma Artificial Intelegence Dalam Pembuatan Konten Aplikasi Tiktok Untuk Meningkatkan Penjualan - Mahendra, Yusril Ihza; Sriyono, Sriyono (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The development of technology and digitalization has had a significant impact on business people and content creators, including business people and content creators in the Malang area. Marketing activities, including branding, now utilize various digital media such as blogs, websites, email, and social networks. This is supported by social media that is very popular with the public such as the Tiktok application. The Tiktok application is currently often used as digital marketing. For example, such as promoting a new product, make-up products, food, education and health. This study aims to analyze data analysis technology and AI Algorithms on optimizing TikTok content to increase sales and good promotional sustainability through the TikTok application in Malang City. The population and sample of this study were business people and content creators/Tiktokers who made sales through the TikTok application as a promotional media as many as 100 respondents. The type of data used in this study is primary data. Data collection method using questionnaires and processed using Partial Least Square (PLS) analysis tools. The results of the study indicate that Data Analysis Technology has a positive effect on purchasing decisions/increasing Sales, AI Algorithms in the Tiktok application have a positive effect on purchasing decisions/increasing Sales, Tiktok Content has a positive effect on purchasing decisions/increasing Sales, Data Analysis Technology has a positive effect on Tiktok Content optimization, AI Algorithms have a positive effect on Tiktok Content optimization, Tiktok Content mediates the influence of Data Analysis Technology on Purchasing Decisions, Tiktok content mediates the influence of AI Algorithms on Purchasing Decisions.